Aromatic Herbs of the Lamiaceae Family as Functional Ingredients in Wheat Tortilla - Kamila Kulbat-Warycha; Kinga Stoińska; Dorota Żyżelewicz (Applied Sciences, 2024)
The rationale for this research is the investigation of the potential health benefits as well as the antibacterial and antifungal properties of selected aromatic plants from the Lamiaceae family, which may lead to the development of improved functional foods. The present study investigated the effects of incorporating dried aromatic plants Thymus vulgaris, Thymus serpyllum, Thymus × citriodorus, Origanum vulgare and Rosmarinus officinalis at a concentration of 1% in refined wheat flour and wholemeal flour on the production of functional tortillas. Sensory analysis was employed to identify the optimal 1% addition, with the objective of achieving a favorable flavor and aroma profile. It was hypothesized that this addition would affect water activity, moisture, texture, color, antioxidant content and phenolic content, thereby enhancing the tortillas as a source of bioactive compounds. The results indicated that the type of flour used had a significant impact on the water activity of the tortillas, with wholemeal flour resulting in higher water activity than refined flour. The water activity ranged between 0.735 and 0.821, while the water content remained relatively stable. The water activity in whole-grain tortillas was significantly higher than that of refined flour tortillas, with a value exceeding 0.8, which makes them susceptible to mold growth and the production of mycotoxins. The sensory evaluations indicated that the enriched refined flour tortillas with common thyme (Thymus vulgaris), lemon thyme (Thymus × citriodorus) and rosemary (Rosmarinus officinalis) were rated highly; a similar result was observed for the whole-grain tortillas enriched with wild thyme (Thymus serpyllum) and lemon thyme. The whole-grain tortillas with rosemary were rated the highest of all the tortillas. The addition of aromatic plants increased the phenolic content and the antioxidant potential, depending on the flour type and the plant used. The addition of wild thyme and rosemary resulted in a significant increase in the phenolic content of wheat tortillas, while all enriched whole-grain tortillas exhibited a higher phenolic content than the control samples. The highest phenolic content in whole-grain tortillas was found in those fortified with rosemary, oregano and wild thyme. The highest antioxidant content was recorded in tortillas prepared with rosemary, irrespective of whether the flour used was refined or wholemeal. Fourteen phenolic compounds were tentatively identified in aromatic plants tested. The main phenolic compounds in Origanum vulgare were flavonoids. Rosmarinic acid was the dominant phenolic compound in rosemary and all thyme species, reaching the highest level in rosemary. Such high levels of rosmarinic acid may be responsible for the high antioxidant and total phenolic contents observed in rosemary extracts and also in tortillas when this plant is included in the recipe. The results of this study indicate that selected aromatic plants, particularly rosemary, have the potential to be utilized as functional ingredients in bakery products. By incorporating dried aromatic plants from the Lamiaceae family into wheat flour tortillas, food manufacturers can create products that not only taste better but also provide added health benefits. The use of selected herbs can improve the nutritional profile of tortillas by increasing antioxidant properties and, due to the properties of herbs, extend the shelf life of the product.